The Impact of Halal Destination Attributes, Experience Quality, and Local Behaviour on Muslim Tourist Satisfaction in Lombok: Moderation Destination Image - Fahira, Khadhiya; Qodhari, Dafelia; Azhar, Jeihan Ali (Universitas Muhammadiyah Yogyakarta, 2025)
The main issue in developing halal tourism destinations is the limited understanding of the factors significantly influencing Muslim tourist satisfaction. This is crucial, considering the vast potential of the halal tourism sector in Lombok as a premier destination. This study examines the influence of Halal Destination Attributes, Experience Quality, and Local Behavior on Muslim Tourist Satisfaction in Lombok, considering Destination Image as a moderating factor. The research employed a quantitative approach, using a questionnaire survey distributed to 300 Muslim tourists who had visited Lombok. Data were analyzed using Partial Least Square-Structural Equation Modelling (PLS-SEM). The results showed that Experience Quality and Local Behavior significantly positively affected Tourist Satisfaction. In contrast, Halal Destination Attributes did not show a significant influence. Moreover, Destination Image could not moderate the impact of Halal Destination Attributes, Experience Quality, and Local Behavior on Muslim Tourist Satisfaction. These findings imply that destination managers should prioritize enhancing tourist experiences and fostering positive interactions with local communities to boost satisfaction, particularly in halal tourism. Although the availability of halal facilities is essential, the study suggests that the quality of the overall tourist experience and the behavior of local residents are more critical in shaping satisfaction. This highlights the need for targeted training programs for local communities and service providers to ensure high-quality, memorable experiences for Muslim tourists. Furthermore, future marketing efforts should focus on the experiential aspects of tourism rather than solely relying on promoting halal attributes.